Evaluasi Sensoris Odor Bubuk Merica Hitam (Pipernigrum L) selama Penyimpanan dengan Olfaktometer Statik - Indyah Sulistya Utami; Tranggono Tranggono; Pudji Hastuti (agriTECH, 2005)
The purpose of the study was to enhance objectivity of sensory evaluation by static olfactometry of black pepper powder odor. Five trained assessors evaluate periodically the odor of black pepper powder stored at 50Â°C during 30 days by test tube and static olfactometry.. Individual repeatability of assessors was higher by static olfactometry than by the test tube. The group perfomed better in discriminating odor character changes using static olfactometry than test tube. They were able to detect an unfamiliar odor but unable to describe it as indicated by the low reproducibility. It follows that static olfactometry can be use as a tool to discriminate black pepper powder character odor changes.